Closure of large alveolar defect by maxillary alveolar distraction using a vector-controlled distractor appliance in cleft patients: A pilot study - Navneet Singh; Tulika Tripathi; Sujata Mohanty; Priyank Rai; Neha Bhutiani (Elsevier, 2021)
Objective: To assess the treatment outcome of custom made maxillary transport distractor appliance for closure of large alveolar clefts. Method: A pilot study was conducted on 12 large alveolar cleft defects present in 11 non-syndromic cleft lip and palate patients (1 bilateral and 10 unilateral) in the age group of 16-25 years. All the subjects underwent pre-surgical orthodontics followed by alveolar distraction using custom-made distractor appliance. Study models, lateral cephalogram, panoramic radiograph and cone beam computed tomograms were obtained pre-surgically (T0) and after distractor removal (T1). The reduction in the width and volume of the alveolar cleft defect and change in the mesiodistal axial inclination of the teeth in transport segment following distraction were recorded. P value ​< ​0.05 was considered statistically significant. Results: Significant reduction in cleft width (9.18 ​mm), volume (89.82 ​mm3) and the change in the mesiodistal axial inclination of the teeth in the transport segment (3.05°) (P ​< ​0.05) were observed. SNA (1.75°), ANB (1.58°), maxillary length (1.58 ​mm), upper incisor inclination (3°) and distal movement of anchorage teeth (0.95 ​mm) also showed significant change (P ​< ​0.05). Conclusion: The custom-made tooth borne distraction appliance successfully closed the large alveolar cleft defect with minimal or no inadvertent effects on the oral tissues.